Service learning in Information Science : Web for the blind - Basrak, Bojan; Matić, Sanja; Mikelić Preradović, Nives (2007)
The biggest problem to blind and visually impaired people poses the integration in various aspects of the social life. Since computer technology with its dominantly visual interface increasingly becomes the prime media for communication, these people are faced with a new obstacle – the ability to work on a computer and use it to communicate with others. Technologies that enable the blind to use the computer do exist, both hardware and software, but they have difficulty learning to use them. The reason for this is lack of standardized educational program so that computer education of blind is usually left to themselves and a few associations that do not have sufficiently qualified staff for such a task. Our service learning project offers the first step to possible solution of the current situation. Service learning is a methodology where learning occurs when students apply what they learn to community problems. It was introduced into information science curriculum in the academic year 2006/07 for the first time in Croatian University with the goal to transform the old teaching style, give the final year students more place to apply the theory they learned through the study and, most important, to provide an important service to the local community. “ Web for the Blind” is the service learning project that provides a first step towards an optimal solution. The main goal of this student project was to establish an adequate model on which all future projects in this field could be based. At the moment “ Web for the Blind” is a stand-alone application that provides the blind and visually impaired with the guides on how to install a web browser, familiarizes them with its interface and gives them some basic information on surfing the web. The application can be used without a mouse and with or without screen-reader software because it contains the tutorials in textual and audio format. The next phase of the project involves intensive testing in the field. It is to be presented to as much users as possible for the evaluation purpose. Finally, the contents of the tutorials need to be gradually updated in both quality and quantity.
Projekt MZOS
Projekt MZOS
ENG